Pemenuhan Baku Mutu Air Limbah sebagai Pemanfaatan untuk Aplikasi Penyiraman ke Ruang Terbuka Hijau Wisata Air di Kabupaten Malang - Muhammad Arfandhani Arifin; R Mohammad Alghaf Dienullah (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
Malang Regency is known as a strategic location with considerable potential as a tourism destination in Indonesia. According to data released by the Central Bureau of Statistics, Malang Regency has recorded 267 tourist destinations spread across 33 districts. This study uses data from one water tourism destination, referred to as Tourism Site X, which focuses on the management and development of recreational areas, including swimming pools, bathing facilities, water attractions, artificial lakes, as well as the management of recreational parks and family facilities such as playgrounds, seating areas, and recreational and educational facilities. Tourism Site X is located in Pakis District, Malang Regency. The reuse of treated wastewater as a non-potable water source for irrigating green open spaces represents a crucial strategic approach to conserving water resources, particularly in water tourism areas such as Tourism Site X, which require substantial water supplies. In practice, the wastewater generated in Tourism Site X mainly originates from domestic sources, including activities such as cleaning swimming pool areas and animal enclosures, toilet usage, and food court operations. This study aims to assess whether the quality of treated wastewater from the wastewater treatment process at Tourism Site X complies with the required standards for green open space irrigation, in accordance with the Regulation of the Minister of Environment/Environmental Control Agency of the Republic of Indonesia Number 11 of 2025 concerning Wastewater Quality Standards and Wastewater Treatment Technologies for Domestic Wastewater, as well as to identify parameters that need to be reduced or eliminated.